Automata, languages and programming proceedings - Caires Luis ed.; International Colloquium, ICALP 2005 on Automata, Languages and Programming; International colloquium, ICALP 2005 on automata, languages and programming Lisbon, Portugal 11-15 Jul 2005 (Berlin Springer-Verlag, 2005)
The papers address all current issues in theoretical computer science and are organized in topical sections on data structures, cryptography and complexity, cryptography and distributed systems, graph algorithms, security mechanisms, automata and formal languages, signature and message authentication, algorithmic game theory, automata and logic, computational algebra, cache-oblivious algorithms and algorithmic engineering, on-line algorithms, security protocols logic, random graphs, concurrency, encryption and related primitives, approximation algorithms, games, lower bounds, probability, algebraic computation and communication complexity, string matching and computational biology, quantum complexity, analysis and verification, geometry and load balancing, concrete complexity and codes, and model theory and model checking.
Keywords: Automata theory; Computer programming languages